Mitotic activity of anti-histone H1 sIgA-antibodies from milk of healthy mothers - Starykovych, M.O.; Stoika, R.S.; Kit, Yu.Ya. (Вiopolymers and Cell, 2013)
Aim. Earlier, we have shown that antibody (AT) preparations obtained by precipitation with 50 % ammonium sulfate from milk of some healthy mothers possess pro-proliferative activity toward transformed and tumor cells in vitro (Kit et al., 2008). We hypothesized that this effect is associated with the presence of the anti-histone H1 sIgAs in AT preparations. Methods. To check this hypothesis, we obtained electrophore- tically homogeneous anti-histone H1 sIgAs from milk of healthy mothers by sequential chromatography on protein A-Agarose, protein G- Sepharose and histone H1-Sepharose respectively. These Ab were tested on a proliferative activity toward human T-leukemia Jurkat and human melanoma SK-MEL cells. Results. It was found that anti-histone H1 sIgAs are able to stimulate proliferation of both tumor cell lines. Mitotic effect of these AB was confirmed with an increase of signal proteins involved in cell proliferation (c-Myc, MAP-and cdc2-protein kinases), detected by Western-blot analysis. We also studied the antigenic reactivity of anti-histone H1 sIgAs toward SK-MEL cell proteins. It was observed that these AB possessed an affinity for a number of melanoma cell proteins with molecular masses of 60, 55, 48 and 38 kDa. Conclusions. It has been found that anti-histone H1 sIgA antibodies can stimulate proliferation of human T-leukemia Jurkat and human melanoma SK-MEL cells in vitro. The cross reactivity of these AB could serve as an explanation of their mitotic activity toward the target cells. Мета. Раніше нами показано, що препарати антитіл (АТ), отримані з молока деяких клінічно здорових породіль осадженням 50 %-розчином сульфату амонію, володіють проліферативною активністю щодо трансформованих і пухлинних клітин in vitro (Кіт Ю. та ін., 2008). Ми припустили, що мітотична активність цих препаратів АТ може бути пов’язана з присутністю у них анти-гістон Н1 sIgA-антитіл. Методи. Для перевірки цієї гіпотези з молока клінічно здорових породіль методом постадійних хроматографій білків на білок А-агарозі, білок G-сефарозі і гістон Н1-сефарозі одержано електрофоретично гомогенні анти-гістон Н1 sIgA і досліджено їхній вплив на життєздатність Т-клітин лінії Jurkat лейкозу людини та клітин лінії SK-MEL меланоми людини. Результати. Встановлено, що анти-гістон Н1 sIgA стимулюють проліферацію клітин лінії Jurkat, а також клітин лінії SK-MEL in vitro. Мітотичний ефект цих АТ підтверджено імуноблотингом за зростанням у клітинах рівня деяких сигнальних білків, залучених до проліферації (c-Myc, MAP- і cdc2-протеїнкінази). Нами також досліджено антигенну реактивність анти-гістон Н1 sIgA щодо білків лізатів клітин SK-MEL. Визначено, що ці АТ виявляють спорідненість до низки білків з молекулярною масою 60, 55, 48 і 38 кДа. Висновки. Показано, що анти-гістон Н1 sIgA-антитіла здатні стимулювати проліферацію Т-клітин ліній лейкозу Jurkat та меланоми SK-MEL людини in vitro. Мітотична дія цих АТ може бути пов’язана з їхньою перехресною імунореактивністю. Цель. Ранее нами показано, что препараты антител (АТ), полученные из молока некоторых клинически здоровых рожениц осаждением 50 %-м раствором сульфата аммония, обладают пролиферативной активностью в отношении трансформированных и опухолевых клеток in vitro (Кот Ю. др., 2008). Мы предположили, что митотическая активность этих препаратов может быть связана с присутствием у них анти-гистон Н1 sIgA-антител. Методы. Для проверки этой гипотезы из молока клинически здоровых рожениц методом постадийной хроматографии белков на белок А-агарозе, белок G-сефарозе и гистон Н1-сефарозе получены электрофоретически гомогенные анти-гистон Н1 sIgA и исследовано их влияние на жизнеспособность Т-клеток лейкоза человека линии Jurkat и клеток меланомы человека линии SK-MEL. Результаты. Установлено, что анти-гистон Н1 sIgA стимулируют пролиферацию клеток линии Jurkat, а также клеток линии SK-MEL in vitro. Митотический эффект этих АТ подтвержден иммуноблоттингом по возрастанию в клетках уровня некоторых сигнальных белков, вовлеченных в пролиферацию (c-Myc, MAP- и cdc2-протеинкиназы). Нами также исследована антигенная реактивность анти-гистон Н1 sIgA к белкам лизатов клеток SK- MEL. Определено, что эти АТ проявляют сродство к ряду белков с молекулярной массой 60, 55, 48 и 38 кДа. Выводы. Показано, что анти-гистон Н1 sIgA-антитела способны стимулировать пролиферацию Т-клеток лейкоза линий Jurkat и меланомы SK-MEL человека in vitro. Митотическая активность этих АТ может быть связан с их перекрестной иммунореактивностью.